(untitled) (Journal of the College of Education for Women, 2019)
The present study attempts to give a detailed discussion and analysis of parenthetical constructions in English and Arabic, the aim being to pinpoint the points of similarity and difference between the two languages in this particular linguistic area.The study claims that various types of constructions in English and Arabic could be considered parenthetical; these include non-restrictive relative clauses, non-restrictive appositives, comment clauses, vocatives, interjections, among others. These are going to be identified, classified, and analyzed according to the Quirk grammar - the approach to grammatical description pioneered by Randolph Quirk and his associates, and published in a series of reference grammars during the 1970s and 1980s, notably A Grammar of Contemporary English (1972) and its successor A Comprehensive Grammar of the English Language in1985. Reference will, however, be made, wherever necessary, to the principles, techniques and terminology of other models of grammar. The method is, thus, more or less, eclectic. The concluding part of the research offers the main findings of the study.